ANALISIS BIAYA PRODUKSI FURNITURE KAYU JATI PADA INDUSTRI USAHA KECIL DAN MENENGAH (UKM) DI PERABOT BERDIKARI JAYA JEPARA ASLI, PEKANBARU - Suryaningsih, Suryaningsih; Sulaeman, Rudianda; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
Teak wood furniture is one of the products of teak wood that much in demand. Currently, the development of teak wod furniture business, especially payung sekaki sub-district, has aserious challenge related to the availability of raw materials. Dearea sod availability of raw materials directly affects production costs. Need to do research on production cost analysis of teak wood furniture in perabot Berdikari Jaya Jepara Asli, Pekanbaru. The purpose of this resource is total production cost is Rp.1.078.711.500,00 and total revenue Rp. 1.234.600.000,00 so that profit is Rp. 156.888.500,00. R/C ratio analysis indicates that the industry is economically suitable which 1,145 point and the industry BEP point is Rp. 666. 563.405.00.Â Keywords: teak wood industry, production cost, R/C ratio, Break even point (BEP)Â